Online Citizen Reporting on Urban Maintenance: A Collection, Evaluation and Decision Support System - Blečić, Ivan; Canu, Dario; Cecchini, Arnaldo; Trunfio, Giuseppe Andrea (TeMA - Journal of Land Use, Mobility and Environment, 2014)
We present an online support system for urban maintenance which: 1. lets citizens directly report neighbourhood issues which may require attention from the urban maintenance services: 2. evaluates the priority of reported issues; 3. allows the allocation and management of resources and workforce on solving issues and 4. permits public tracking of their status. The web application was entirely developed using low-cost Google cloud services, with the advantage of low deployment and hosting costs and practically no systems administration costs, a highly replicable and transferrable solution, and a rapid development process relying on robust Google services. The model for evaluating priority of reported issues is based on the the ELECTRE TRI rating method. In the paper we present the system’s standard workflow, the evaluation model and the implementation details. We also discuss its possible more general implications for fostering and supporting citizens participation. Unlike many existing platforms for citizens reporting of maintenance issues, our system incorporates an explicit and publicly accessible evaluation model to prioritise issues and assign resources for their solution. This, we argue, is a crucial prerequisite for the principles of transparency, publicity, accountability and equity be observed by municipal governments.